2009
DOI: 10.1007/s12046-009-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Bio-functionalization of silicon nitride-based piezo-resistive microcantilevers

Abstract: Methods of bio-functionalize silicon nitride involve process steps to convert it into an oxynitride via plasma implantation techniques. Such methods can potentially damage microstructures such as cantilevers. In this paper, we report successful bio-functionalization of Hotwire CVD silicon nitride-based piezo-resistive cantilevers without any oxygen plasma treatment. Process to fabricate such structures and to bio-functionalize them is discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Sometimes multiple layers of linking molecules are utilised to increase the bonding strength. Biotin-streptavidin [19,20], antibody-antigens [21][22][23] and aptamers [24,25] are among the most commonly used molecule pairs for surface functionalisation studies. Furthermore, using self-assembled-monolayers (SAMs) is becoming a popular choice in the recent literature [26][27][28] as well as sandwich-type surface functionalisation and nanomaterials [17,29].…”
Section: Terminology and Trendsmentioning
confidence: 99%
“…Sometimes multiple layers of linking molecules are utilised to increase the bonding strength. Biotin-streptavidin [19,20], antibody-antigens [21][22][23] and aptamers [24,25] are among the most commonly used molecule pairs for surface functionalisation studies. Furthermore, using self-assembled-monolayers (SAMs) is becoming a popular choice in the recent literature [26][27][28] as well as sandwich-type surface functionalisation and nanomaterials [17,29].…”
Section: Terminology and Trendsmentioning
confidence: 99%
“…Immobilisation layer is applied over the structural layer of biosensing cantilevers which are used to sense the chemical substances, antibodies, explosives etc. The immobilisation layer is a chemical which reacts with the required analyte e.g., Palladium coating absorbs hydrogen and expands [10,11], Myoglobin antibody is used to detect myoglobin [12].…”
Section: Materials and Manufacturing Aspecfsmentioning
confidence: 99%
“…This paper, with a in detail in this paper. comprehensive list of references (104 references were listed), dealt with various aspects of cantilever based Biofunctionalization microcantilevers with sensors such as methods of use, method of secondary silicon nitride based piezoresistive element is transduction, biosensing applications and a future presented in [12]. The schematic of the piezoresistive direction.…”
Section: Applications In Sensorsmentioning
confidence: 99%
“…At present, there seems to be some obstacles to realize full potential of cantilever‐based biosensor. Firstly, instead of complex and expensive optical method for measuring the deflection of cantilever 69, electrical method has been developed by fabricating the cantilever with the silicon (or silicon compound) piezoresistance, where the deflection can be translated into electrical signal for simple and easy measurements 1013. However, it has been found that the signal of p + ‐Si piezoresistance is not stable during measurement due to its high temperature coefficient of resistance (TCR) 14.…”
Section: Introductionmentioning
confidence: 99%